Multimodal and Digital Literacy as New Concepts in Education - Vidosavljević, Milena M. (Collection of Papers of the Faculty of Philosophy in Priština, 2022)
The digital age requires each individual to redevelop new skills and many literacy skills in order to function in modern society. Therefore, new concepts are emerging in education that explain what all the skills are necessary in order to adequately perform certain activities in the online environment. One of the modern concepts is multimodality, which is inevitably accompanied by modes, multimodal literacy, and digital, as well as broader literacy. Multimodality is a communication phenomenon that relies on the use of modes, i.e., semiotic resources, whose role is to create meaning. Namely, mods include images, charts, sounds, colours, audio, videos, maps and so on. Their function is to help digital texts convey a specific message in an online environment. In all this, the key role is played by multimodal literacy, which is the ability to successfully work with texts that include different modes, as well as digital literacy, which includes the ability to search, locate, select and analyse digital information. Having in mind that both literacies are interconnected and complementary, the aim of this paper is to draw attention to the mentioned concepts as well as to present their importance for the realization of multimodality in education.
Keywords: literacy; multiliteracies; multimodality; multimodal literacy; digital literacy